KELAYAKAN DINAS KESEHATAN DALAM PENGELOLAAN JAMINAN KESEHATAN DAERAH DI KABUPATEN KUTAI BARAT - , Marhadyn ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In every area, the dynamic development of Jamkesda is very variatif. This is reflected from manajement council of Jamkesda, few of area directly managed by the regional organization on the local district through the task force in the Health Department level or by the implementing council that's implemented by UPTD (Technical Implementation Unit Area). But in other side, there is a part of area submit the Jamkesda management to private insurers like PT. ASKES. To ensure the implementation of Jamkesda by local government independently, it needs feasibility assessment SKPD (Unit Area Of Device). The goal is to assessing the feasibility of the Health Department District West Kutai in Jamkesda management which reviewed from human resources aspect, financial aspect and regulator stakeholder commitment. The method of this research is case study with holistic single case design that aims for exploration how the appropriateness Health Department West Kutai District in Jamkesda Management, with the research subject is stakeholder who have a role in determination of policy development Jamkesda in the executive and legislative scope. Analysis unit of this research is Health Department Of West Kutai District. The results of this research is the management of Jamkesda on the West Kutai District it is not feasible managed by the Health Department of West Kutai District with consideration there is not enough available human resources that have competency and cannot work full time to managed the Jamkesda. Another reason is the readiness financial for financing Jamkesda is not enough for early development Jamkesda. The third reason is there is not avalaible legal products in the district level that garanty management in privately, this is reflecting there is no strong commitment from the stakeholder to develop the Jamkesda in West Kutai District.